1975
DOI: 10.1002/pssa.2210290107
|View full text |Cite
|
Sign up to set email alerts
|

The range of homogeneity of VO2 and the influence of the composition on the physical properties. II. The change of the physical properties in the range of homogeneity

Abstract: The electrical resistivity (semiconductor–metal transition), the thermoelectric power, and the magnetic susceptibility of well‐characterized VO2 monocrystals and powdered samples in the range of homogeneity were measured. The physical properties gave no hint of an extension of the range of homogeneity towards oxygen excess. An oxygen deficit (VO1.994) strongly influence the semiconductive properties of VO2 below the phase transition temperature, but hardly influences the metallic properties above the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 13 publications
(1 reference statement)
5
20
0
Order By: Relevance
“…For example, Kimizuka et al (20) reported that from VO to VO the changes of resistivity were from 1.3;10 to 2;10 accompanied with the variances of transition temperatures from 63 to 713C. However, BruK ckner et al (21) observed that from VO to VO the changes of resistivity were from 6.3;10 to 1.3;10 with the variances from 58 to 693C. Phase transition resistivity for polycrystalline VO has not been reported so far, and the e!ects of various stoichiometry VO in both monocrystals and polycrystals on phase transition heat also have not been reported.…”
Section: Transition Behavior Of Various Stoichiometry Vomentioning
confidence: 93%
“…For example, Kimizuka et al (20) reported that from VO to VO the changes of resistivity were from 1.3;10 to 2;10 accompanied with the variances of transition temperatures from 63 to 713C. However, BruK ckner et al (21) observed that from VO to VO the changes of resistivity were from 6.3;10 to 1.3;10 with the variances from 58 to 693C. Phase transition resistivity for polycrystalline VO has not been reported so far, and the e!ects of various stoichiometry VO in both monocrystals and polycrystals on phase transition heat also have not been reported.…”
Section: Transition Behavior Of Various Stoichiometry Vomentioning
confidence: 93%
“…At 340 K, VO 2 exhibits a transition from a monoclinic semiconductor (M 1 ) phase to a metallic phase with rutile structure (R) . The phase transition is accompanied by a change from an antiferromagnetic to a paramagnetic spin state .…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information on the experimental conditions was given in an earlier paper of ours [12].…”
mentioning
confidence: 99%